OPTIMIZATION OF MULTI STOREY SPACE STEEL FRAMES, MATERIALLY AND GEOMETRICALLY PROPERTIES NON-LINEAR - Esen, Yueksel; Ulker, Mehmet (Gazi Univ, Fac Engineering Architecture, 2008)
In this study, optimization of space steel frames exposed to seismic loads was carried out by taking into consideration both materially and geometrically nonlinear behaviours via the ANSYS packed program. By taking into account the buckling estimations, the buckling constraints were applied to the optimization technique. For the nonlinear behaviour of the material, the bilinear cinematic hardness model was used and the buckling formulation given in TS 648 was taken in the solutions. For a dynamic solution technique, Newmark method and for the nonlinear solution algorithm, Newton-Raphson methods were used. Solutions were found by preparing subroutine in APDL (Ansys Programming Design Language) coding language of ANSYS packed program.
Keywords: Space frame; non-linear Analysis; optimization; ANSYS